DEDUCTIBILITY OF CONTRIBUTIONS TO VOLUNTARY PRIVATE PENSIONS - LILIANA MUNTEAN; ANA-PETRINA STANCIU (Annals of the University of Petrosani: Economics)
The present paper approaches the notion of public and private pension in Romania. Pension can be seen in terms of a replacement income to individuals whose age no longer affords to operate in the labour market. Pension reform in Romania has allowed besides the public pension system, called Pillar I, which is a distributive system based on solidarity between generations also a private pension system that records the contributions of participants in individual accounts, based on capitalization, investment and accumulation of these contributions.